ASSESSMENT OF PROTEIN, GLYCOGEN AND ACTIVITY OF PHOSPHATASES OF LABEO ROHITA IN RESPONSE TO PHYSICOCHEMICAL PARAMETERS OF LAKES OF BANGALORE - BELA ZUTSHI; NAZIMA NOOR; G. SREEKALA (The Bioscan, 2015)
The analysis of physico- chemical parameters of two polluted lakes, Vengaiah lake (lake A) and Yellamallappa Chetty lake (lake B) of Bangalore was conducted with Hebbal fish farm taken as the control site. The effect of outcome of the assessed data was observed on the bio-molecules (proteins and glycogen) and enzyme activity (acid phophatase - ACP and alkaline phophatase - ALP) in the tissues - gill, muscle, liver, kidney and brain of Labeo rohita, a freshwater fish reared in the two lakes. A reduction in the levels of proteins and glycogen, and activity of ACP and ALP in the tissues of test fish sampled from lake (B) when compared to those of lake (A) and control was documented. Maximum reduction in percentage of protein content was in the order as; gill>brain>muscle> kidney> liver while glycogen followed the trend as kidney > liver > muscle > gill > brain. Percentage of ACP activity showed decreasing trend in tissues; brain >kidney > liver > gill > muscle but ALP activity showed an equal percentage in brain and liver followed by kidney, gill and muscle. Such alterations indicated stressful condition of the fish due to changes in biochemical constituents, metabolic pathways, dysfunctioning and cellular damage in various tissues to maintain physiological equilibrium which resulted in weakening of fish making it susceptible to diseases and a less nutritive resource. The data was statistically analysed by using graphpad prism.